Annual Report on Exchange Arrangements and Exchange Restrictions 1985. (Annual Report on Exchange Arrangements and Exchange Restrictions; 1985, 1985)
This paper discusses developments in the international exchange rate and restrictive systems. Global output and trade recovered strongly in 1984, as inflation in the industrial countries remained relatively subdued and further progress in developing countries was made in tackling the problem of overindebtedness. Restrictive exchange practices in the form of multiple exchange rates have been substantially reduced in 1984. Multilateral restructurings of obligations have been large in 1983, amounting to some SDR 60 billion, as compared with SDR 6 billion in 1982.